Smart Assessment: A Computer-Based English Assessment System For Junior High School Students in Merauke Integrated With Deep Learning - Sijabat, Survey; Rahim, Abdul (Journal of Authentic Research, 2025)
This study aims to develop and analyze a computer-based Smart Assessment system integrated with a deep learning pedagogical approach for assessing the English language skills of junior high school students in Merauke. The system was implemented using the Quizizz platform as a Computer-Based Test (CBT), incorporating three core principles of deep learning: meaningful learning, mindful learning, and joyful learning. The research employed the 4D development model (Define, Design, Develop, Disseminate) and involved 45 junior high school students during the field implementation phase. Smart Assessment was applied in regular English assessment activities, enabling students to complete tests digitally while teachers monitored performance and results in real time. Several challenges emerged during implementation, including limited internet connectivity, differences in students’ digital literacy levels, and teachers’ initial adaptation to technology-based assessment. Despite these constraints, the system proved effective in facilitating teachers to conduct assessments more efficiently and accurately, while providing immediate and automated feedback that supported students’ reflective learning processes. Item quality analysis was conducted using Classical Test Theory (CTT) with the support of RStudio software. The results demonstrated very high instrument reliability (Cronbach’s Alpha = 0.961). Most test items were classified as having moderate difficulty, with good to very good discrimination power, and all distractors functioned effectively. These findings confirm that the developed instrument meets acceptable psychometric standards for educational assessment. Implementation of Smart Assessment shows strong potential to support objective, efficient, and engaging English language assessment, while enhancing teachers’ assessment practices and improving students’ learning experiences. This system offers a practical and innovative solution for English language assessment in the context of digital and 21st-century education, particularly in remote and border regions.